Blastic Plasmacytoid Dendritic Cell Neoplasm on the Scalp - Sawako Fukushi; Taku Fujimura; Setsuya Aiba (Karger Publishers, 2011)
We describe a 75-year-old Japanese woman with blastic plasmacytoid dendritic cell neoplasm. On her first visit, there were multiple areas of disseminated, elastic hard nodules with multicentric purpura on her scalp. Histopathologically, there were atypical large lymphocytes densely infiltrated through the upper dermis to subcutaneous tissue. Immunohistochemical staining revealed that these infiltrated lymphocytes were CD4, CD56 and vimentin positive. Although we administered several courses of intensive chemotherapy soon after the diagnosis, the patient died 5 months after the first visit.